Comparação da performance acadêmica entre estudantes oriundos de diversos colégios agrícolas no curso de agronomia da UFSM - Wolff, Robert L.; Tonini, Enio (Revista do Centro de Ciências Rurais, 2008)
Uma investigação no fichário dos alunos do Curso de Agronomia da UFSM formados entre 1970 e 1974 indicou que dos 367 alunos formados, 140 provieram de Colégios Agrícolas. Aqueles 140 provieram de 11 Colégios Agrícolas, sendo que 94% desse total vieram de 6 Colégios e os restantes 6%. de outros 5 Colégios. Os colégios Agrícolas de Santa Maria e Ijui contribuiram com 54%, sendo que o de Santa Maria apresentou-a maior oferta com 38%. A análise da performance acadêmica dos estudantes oriundos dos 6 Colégios principals, medida em termos de notas obtidas, mostrou que não há diferenças significativas entre os seis qrupos na performance do vestibular ao nível de 01% de signific$ncia, entretanto, uma diferença significativa foi observada na performance acadêmica ao lonqo do curso ao nível de 05%. Estudantes oriundos dos Colégios Agrícolas de Erechim e Cachoeirinha, apresentaram melhor performance ao lonqo dos oito semestres do curso, respectivamente. Achou-se, também, uma correlação positiva, embora baixa (r=0,34), entre a média do vestibular e a média obtida ao longo do curso.AbstractAn investigation of the records of the Agronomist graduates at UFSM from and including 1970 to 1974 indicates that 140 of the 367 total students previously attended and Agricultural Colegio before entering the UFSM. It was found that the 140 students from Agricultural Colegios came to the UFSM from 11 schools in Rio Grande do Sul. In distribuition, 94 per cent of the 140 students previously attended 6 Colegios, while the remaining 6 per cent came from 5 schools. Fifty-four per cent attended the Agricultural Colegio in either Santa Maria or Ijui. The Agricultural Colegio in Santa Maria was foun to be largest supplier of students, with 38 per cent of the students having previously attended that school. In an analysis of the academic performance of the students from the six major contributing Agricultural Colegios, it was found that there was no significant difference among the six groups in their performance on the vestibular as measured at the 01 confidence level. There was, however, at 05 confidence level, a significant difference observed in the academic performence in course work as measured.by course grades during eight semesters of work. Students from the Agricultural Colegios in Erechim and Cachoeirinha in that respective order, were found to earn the best grades through eight semesters of course work. In an analysis of the mean vestibular scores and mean semesters of course grades during eight semesters of course work, a positive correlation was observed (r=0,34), however the correlation is rather low.